No need for constant help: human IgG2 antibodies have an autonomous agonistic activity for immunotherapy of cancer. - Lux, Anja; Nimmerjahn, Falk (Cancer cell, 2015)
Agonistic antibodies specific for members of the tumor necrosis factor receptor protein family hold great promise for immunotherapy of cancer. In this issue of Cancer Cell, White and colleagues provide evidence that the human IgG2 subclass may represent a superior backbone for the use of these antibodies in human therapy.